The Idea of Moderate Islam in the Media Space for the Social Construction of Religious Moderation in Indonesia - M. Yusuf Wibisono; Wahyudin Darmalaksana (Khazanah Sosial, 2022)
Social media space can shape social construction, including being able to construct moderate Islamic ideas. However, the embodiment of the media space promoted by moderate Islam in shaping the social construction of religious moderation is still questionable. This study aims to discuss the idea of moderate Islam in the media space for the social construction of religious moderation in Indonesia. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the theory of social construction, while the material object is the idea of moderate Islam. The scope of research is the social media space. The rest of this research's context is the social construction of religious moderation in Indonesia. The results and discussion in this study indicate that the social construction of religious moderation in Indonesia is formed based on the social construction of digital media which is framed by moderate Islamic ideas in the social media space of Twitter, Instagram, and Facebook. This study concludes that the idea of moderate Islam in the media has manifested in Indonesia's social construction of religious moderation. This study recommends that Islamic institutions and organizations manage the social media space creatively and innovatively as a solution to mainstreaming religious moderation in Indonesia.